Serbia under the Swastika A World War II Occupation - Prusin, Alexander Victor 1955-2018 (History of Military Occupation Ser, 2017)
Title Page -- Copyright Page -- Contents -- Biographical Note on Key Personalities -- Introduction -- 1 - Background, 1918-1941 -- 2 - Invasion and Occupation -- 3 - Germans and Auxiliaries -- 4 - Collaborationism: Zealots, Conservatives, Conformists -- 5 - Resistance Movements -- 6 - Repression -- 7 - "Serbia is Quiet," 1942-1944 -- 8 - Serbs and Jews -- 9 - Living with the Enemy -- Conclusion -- Notes -- Bibliography -- Index -- Illustrations -- About the Author